Food profile, environmental factors, stunting, and risk of autism among children on Citarum watershed: a preliminary study - Shela Rachmayanti; Asri Chasanah Adisasmita; Retno Asti Werdhani; Wiku B. B. Adisasmito (Universitas Gadjah Mada, 2021)
Purpose: The Citarum River, Indonesia, is one of the most polluted rivers in the world. Despite this, it is still used for community purposes. This preliminary study aims to determine the initial profile and magnitude of the problem in the health ecosystem along Citarum River, which focuses on stunting and the risk of autism associated with food consumption and environmental factors. Methods: Our random sample included children aged <5 years from their households in the Andir and Gajahmekar villages, from September 2018 to September 2019. We interviewed guardians on food consumption and the Modified Checklist for Autism in Toddlers - Revised (M-CHAT-R) questionnaire. The height measurement was interpreted with HAZ WHO-curve. The relationship between variables was analyzed through Chi-square. Results: This study showed that the proportion of stunting and risk of autism was 46.2% and 68%, respectively. Children who consume cow's milk and do not consume tomatoes are more at risk of developing autism. Moreover, subjects that consume chicken and fish from the Citarum riverbank have a higher risk of stunting and autism. Conclusions: Based on this preliminary study, the proportion of stunting and autism in children on the Citarum watershed is higher than the national average. The animal husbandry service authority must consider efforts to maximize this riverside habitat to provide livestock as a source of protein for communities around the river.